Toward high energy ultrashort pulse all-fiber laser with normal dispersion thulium fiber - Chen, Yuhao (Nanyang Technological University, 2022)
“Ultrashort pulse” (also known as “Ultrafast”) fiber lasers have many advantages, which are utilized in a myriad of applications in industrial, micromachining, laser-assisted manufacturing, defense, medical, optical communications, and scientific research. With increasing available peak power and pulse energy, new applications of ultrafast lasers are constantly being discovered such as high precision micromachining, where nano/micro structuring is enabled with much improved quality by the pulse width much shorter than the heat diffusion time of the material. Progress of high energy ultrashort pulse fiber laser technology has been centered the “conventional” wavelength of ~1 μm. This limited access to wavelength defines the type of material the laser can process, mainly metals. Other “unconventional” wavelengths can be down to visible and ultraviolet range, or up to “eye-safe” short-infrared range. At these “unconventional” wavelengths, the ability to laser process other exotic materials such as polymers and semiconductors opens. In the 2 μm wavelength range, there are large water absorption lines, which makes it possible for bio applications. High energy ultrashort pulses generated at wavelengths ~1.7 μm with have huge potential for usage in 3 photon microscopy. The 1.7 μm to 2 μm wavelength range lies within the Thulium emission range. Thus, there is good motivation to develop Thulium ultrafast lasers. Further to developing a laser system, an important consideration is the type of medium the laser is generated in. The main advantages of all-fiber based lasers over Diode Pumped Solid State (DPSS) or Lamp Pumped Solid State (LPSS) lasers is that there are no free-space alignment issues, that the all-fiber configuration is maintenance-free since there are no free-space components to keep clean, and that the fibers and fiber components are able be coiled up to fit in a compact space which increases portability for deployment. These factors allow all-fiber lasers to be easily deployable in the field and industrial settings. Furthermore, in terms of designing, by having the gain medium in the fiber waveguide itself in an all-fiber configuration is able to easily to control the dispersion and nonlinearity by designing the waveguide and fiber lengths with customized dispersion maps to generate ultrashort pulses, while still allowing for high energy ultrashort pulses to be generated and wave guided stably. Hence, the aim is to develop a practical high peak power or high pulse energy ultrashort pulsed all-fiber laser at Thulium wavelength, which can be ultimately readily deployed in material processing and bioprocessing and imaging applications in industry. To develop such a laser system, a dispersion engineered Normal Dispersion Thulium Fiber (NDTF) is designed, fabricated, characterized. The NDTF was successfully deployed in an all-fiber seed oscillator and amplifier in different lengths and configurations including stretcher and/or compressor to optimize output parameters such as lasing wavelength, pulse energy, pulse duration, or peak power. High pulse energy of ~846nJ was achieved by reducing the repetition rate of the seed oscillator and optimizing the length of amplifier. Pulse widths as short as 309 fs was demonstrated by optimizing fiber lengths of stretcher and compressor. A high peak power of ~631 kW was achieved by minimizing the pulse width as much as possible. Finally, a tunable lasing wavelength range from a high of 1900nm to a low of 1693nm was demonstrated by utilizing a natural filtering effect of the NDTF. Adding on to this work, a second generation NDTF is designed and manufactured and deployed in a CW laser cavity to demonstrate the lasing and wavelength tunability. From the results, the NDTF can readily be made into a product for industry use. The results from this work have been published in several papers and conferences, and a Technical Disclosure (TD) has been filed on the invention of the NDTF with potential Patent Filing Consideration. This work was funded by MOE Tier 1 Grant RG 84/18 and industry collaborator Sintec Optronics Pte. Ltd. in conjunction with the Industrial Post-graduate Program (IPP) by Economic Development Board (EDB) of Singapore to contribute to Singapore’s photonics industry.